ANALYSIS OF THE RESISTANCE OF GRAIN PESTS TO PHOSPHINE. REVIEW - G. A. Zakladnoy (Пищевые системы, 2020)
Resistance of stored grain pests to phosphine is a problem that is being treated in many countries of the world. This is due to the fact that this fumigant is the most widely used in the world. The review shows the resistance of a number of major pests to phosphine from the initial to the high degree of resistance due to its importance for practical use in the protection of stored grain. The analysis of the search and use of alternative fumigants has been given, the reasons for their refusal to use them have been formulated. The causes of the emergence of resistant insect populations at high concentrations of phosphine are described and measures to overcome resistance are proposed. It is shown that this circumstance leads to inefficiency of the application of existing fumigation regulations by phosphine in warehouses and elevators, in metal silos, in wagons on the way, in the holds of small-ton and large-capacity vessels in the voyage. It is concluded that only a comprehensive approach to research to identify the causes of the emergence of resistance of stored product pests to phosphine will help to avoid the abandonment of the use of phosphine in Russia and other countries. This circumstance will avoid large losses in the grain industry.